دراسة تاثير اضافة العامل المنشط للسطح دوداكيل بنزين سلفونات الامونيوم التوأميه على مقاومة الانضغاط لخلطة أسمنتية ذات المعالجة الرطبة - عبد الجليل ناظم (University of Thi-Qar Journal of Science, 2008)
In this study we focused on adding (Dodecyl Benzene Ammonium Sulphonate) and this adding was in form of different ratio of these additive to the matrix ofIraqi cement (Om Quasar factory for cement). The prepared samples was inform of cubic and evaluated as they were treated with moisture treatment. Allthe prepared samples had a proportion of 3/1) cement to sand) and in the formof cubes with aside (50 mm) long. The weight rate of (Dodecyl BenzeneAmmonium Sulphonate) to the cement was (1%-8%). The obtained resultsshowed that the cement mixture that had the weight rate of 2% at moisturecuring is the best as it has good mechanical properties (compressive strengthnear to pure samples). Also this kind of surfactant have an opposite effect onmechanical properties and this effect is related to adding ratio and curing time.The effect of surfactant (Dodecyl Benzene Ammonium Sulphonate) works as plasticizer on cement matrix so the application range of used cement speciallyin oil well where these applications need flexible cement with high workability.